Abundance and distribution of climbers in a coastal hill forest in Perak, Malaysia. - Ghollasimood, Sholeh; Ibrahim, Faridah Hanum; Salleh @ Japri, Mohd Nazre; Abd. Kudus, Kamziah (Canadian Center of Science and Education (CCSE), 2012)
Species diversity and density of all climbers were inventoried in five 1-hectare plots (at 45m to 350 m elevations) in a coastal hill forest of Pulau Pangkor in Perak. In addition, we analyzed pattern of community diversity using species richness and evenness. Total of 4901 climbers belonging to 45 species were recorded. Mean climber density was 870 stems per ha. Annonaceae, Connaraceae and Menispermaceae were the most species-rich plant families of climbers followed by Rubiaceae and Leguminosae. Twiners formed the bulk (64%) of climber types followed by hook climbers and tendril, while root climbers were rare. Results from Canonical Corresponding Analysis (CCA) indicate that altitude was the most important factor that influenced the abundance and distribution of climbers.